2022
DOI: 10.1007/s11356-022-23185-4
|View full text |Cite
|
Sign up to set email alerts
|

How do foreign direct investment flows affect carbon emissions in BRICS countries? Revisiting the pollution haven hypothesis using bilateral FDI flows from OECD to BRICS countries

Abstract: Foreign direct investment (FDI) flows from developed to developing countries may increase carbon emissions in developing countries as developing countries are seen as pollution havens due to their lenient environmental regulations. On the other hand, FDI flows from the developed world may improve management practices and advanced technologies in developing countries, and an increase in FDI flows reduces carbon emissions. Most of the existing studies examine the relationship between FDI flows and carbon emissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(33 citation statements)
references
References 94 publications
2
21
0
2
Order By: Relevance
“…Wang Yujing(2022) [25] and others show that FDI puts pressure on environmental quality in the long run, supporting the 'pollution sanctuary' hypothesis. Apergis Nicholas(2022) [26] suggest that FDI flows from Denmark and the UK to the BRICS increase carbon emissions in the BRICS, supporting the "pollution sanctuary" hypothesis. Some scholars have pointed out that FDI causes exports, which in turn leads to imports and further increases carbon emissions in the long run (Ritu Rana, 2019 [27];Dagar Vishal, 2022 [28] ).…”
Section: Related Theories 21 the "Pollution Sanctuary" Doctrinementioning
confidence: 95%
“…Wang Yujing(2022) [25] and others show that FDI puts pressure on environmental quality in the long run, supporting the 'pollution sanctuary' hypothesis. Apergis Nicholas(2022) [26] suggest that FDI flows from Denmark and the UK to the BRICS increase carbon emissions in the BRICS, supporting the "pollution sanctuary" hypothesis. Some scholars have pointed out that FDI causes exports, which in turn leads to imports and further increases carbon emissions in the long run (Ritu Rana, 2019 [27];Dagar Vishal, 2022 [28] ).…”
Section: Related Theories 21 the "Pollution Sanctuary" Doctrinementioning
confidence: 95%
“…Concerning the impact of FDI on environmental pollution, the academic community has formed two hypotheses: the pollution haven hypothesis and the pollution halo hypothesis. The former argues that FDI, through introducing a high-pollution industry in the host country, deteriorates the host country’s environmental quality, and the latter argues that FDI can introduce environmentally friendly products and technology to improve environmental quality [ 59 ]. Thus, the impact of FDI on PM 2.5 pollution is uncertain.…”
Section: Methodsmentioning
confidence: 99%
“…As developing countries are perceived as pollution havens, FDI flows from developed to developing countries may raise CO 2 pollution in developing countries; nevertheless, the movement may enhance management practices and sophisticated technology in developing countries, thereby reducing CO 2 pollution. Similarly, Apergis et al ( 2022 ) contributed to the body of knowledge by assessing the influence of FDI flows on CO 2 pollution in BRICS countries between 1993 and 2012 utilizing bilateral FDI flows from OECD nations. The data demonstrate that FDI flows from Denmark and the UK to BRICS nations enhance CO 2 pollution in BRICS nations, thereby verifying the pollution heaven theory, while France, Germany, and Italy lowered CO 2 pollution in BRICS nations, demonstrating the pollution halo effect.…”
Section: Theoretical Background and Empirical Reviewmentioning
confidence: 99%
“…And the study of Saint Akadiri et al ( 2020 ) examined the links between GPR–tourism–economic growth in Turkey and discovered that GPR decreases the number of international tourists and economic growth in the country. Using the method of forecast error decomposition, Payne and Apergis ( 2022 ) found that GPR in the USA explains a considerable proportion of the forecast error variance associated with overseas travel and economic policy uncertainty. Ming and Liu ( 2021 ) investigate the impact of GPR on China’s tourism business and suggest that it significantly affects tourism.…”
Section: Theoretical Background and Empirical Reviewmentioning
confidence: 99%